(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Objective To develop and validate a simple, precise, accurate, and stability-indicating reverse-phase high-performance liquid chromatographic (RP-HPLC) method for estimation of Lercanidipine in bulk and tablet dosage forms. Methods Chromatographic separation was achieved using an Enable C18 column (250 mm × 4.6 mm, 5 μm) and a mobile phase consisting of phosphate buffer (pH 3.5): acetonitrile (45:55 v/v) at a flow rate of 1.0 ml/min. UV detection was carried out at 238 nm. The method was validated according to ICH Q2(R1) guidelines for linearity, precision, accuracy, robustness, LOD and LOQ. Forced degradation studies were performed under acidic, basic, neutral, oxidative, thermal and photolytic conditions as per ICH Q1A(R2). Results Lercanidipine exhibited a retention time of 5.42 min. Linearity was observed in the range of 5–100 µg/ml (r² = 0.9998). The mean % recovery was 99.12% and %RSD for repeatability was < 0.5%. LOD and LOQ were found to be 0.28 µg/ml and 0.86 µg/ml, respectively. The drug was found stable under acidic neutral and thermal conditions but degraded significantly in basic, oxidative and photolytic environments. Conclusion The developed RP-HPLC method is simple, robust, and stability-indicating as per ICH guidelines and suitable for routine quality control of Lercanidipine in bulk and tablet dosage forms.